Smart City Implementation Towards Indonesia Emas 2045 - Venita Prasetyadewi; Achmad Nurmandi; Helen Dian Fridayani (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
This research aims to find out how the implementation of the Smart city concept in Indonesia towards the vision of the Golden Indonesia 2045. This concept is considered to be a solution for Indonesia in advancing all its sectors. The method used in this research is descriptive qualitative method. This research utilizes secondary data sources derived from mass media such as digital news and is processed and analyzed using Nvivo 14 software. Based on the results of this study, the application of the smart city concept in Indonesia has been effectively implemented. Stakeholders show their seriousness in realizing the vision of Indonesia Emas 2045. This is evidenced by the many innovations in each sector that support the implementation of smart cities. These innovations include the launch of applications in the government service sector, as well as innovations in the transportation sector. However, in this study, the application of the smart city concept has imbalances in each sector, such as in the government sector which has the highest index with the Environment sector which has the lowest index in its implementation. This is because the implementation of smart cities in Indonesia still has shortcomings in several sectors that must be addressed if the vision of Indonesia Emas 2045 is to be realized.